The Composition and Performance of Iron Ore Tailings in Steel Slag-Based Autoclaved Aerated Concrete - Hao Zhou; Yang Jiang; Jiaqing Wang; Houhu Zhang; Binbin Qian; Bing Ma; Yueyang Hu (Buildings, 2023)
Iron ore tailings (IOTs) are byproducts of the iron mining industry that have gained significant attention in recent years due to their potential for comprehensive utilization. This study investigates how blending steel slag with IOTs (a siliceous raw material) instead of lime (a calcareous raw material) affects slurry foaming properties, mechanical properties, and reaction mechanisms of autoclaved aerated concrete (AAC). The results indicate that the sample containing 24% IOT content exhibited the best performance, with a bulk density of 640 kg/m3 and a compressive strength of 4.1 MPa. In addition, IOTs not only served as a filling material but also acted as a carrier for the growth of tobermorite. Tobermorite was combined with the unreacted iron tailing and its neighboring tobermorite to form a cohesive whole. This study provides valuable insights into the potential for IOTs to improve the properties of AAC when used as a supplementary material. The findings also suggest that the comprehensive utilization of IOTs and other industrial byproducts have the potential to contribute to the development of sustainable building materials and reduce the environmental impact of the mining industry.